2014
DOI: 10.1371/journal.pone.0114562
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Non-Invasive Semi-Quantitative Bioluminescent Imaging Method for Monitoring of an Orthotopic Esophageal Cancer Mouse Model

Abstract: Orthotopic models of various types of tumors are widely used in anti-tumor therapeutic experiments in preclinical studies. However, there are few ways to appropriately monitor therapeutic effect in orthotopic tumor models, especially for tumors invisible from the outside. In this study we aimed to establish a non-invasive semi-quantitative bioluminescent imaging method of monitoring an orthotopic esophageal cancer mouse model. We confirmed that the TE8 esophageal cancer cell line implanted orthotopically into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Furthermore, there are a few studies, which have reported orthotopic metastatic mouse models of esophageal cancer, however, of our knowledge, other orthotopic metastatic mouse models of cocultured EC with CAFs have not been reported . We have established and reported this esophageal orthotopic xenograft model, in which tumor volume and metastatic activity were evaluated by luciferase emission . In our study, we successfully transfected TE4 cells with luciferase and applied TE4‐luc cells to evaluate metastatic activity.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there are a few studies, which have reported orthotopic metastatic mouse models of esophageal cancer, however, of our knowledge, other orthotopic metastatic mouse models of cocultured EC with CAFs have not been reported . We have established and reported this esophageal orthotopic xenograft model, in which tumor volume and metastatic activity were evaluated by luciferase emission . In our study, we successfully transfected TE4 cells with luciferase and applied TE4‐luc cells to evaluate metastatic activity.…”
Section: Discussionmentioning
confidence: 97%
“…67,68 Orthotopic transplantation as alternative mouse model seems to be possible, but also showed some drawbacks before. [69][70][71][72] For example, Gros and colleagues 69 injected primary EAC cells into the submucosa of the abdominal esophagus by an invasive surgery technique, but only peritoneal carcinomatosis without formation of primary tumors was observed in this model. Still, our study provides a first comprehensive in vitro approach and insight to show cancer cell-selectivity for the entity of esophageal cancer by comparing non-neoplastic esophageal Het-1A cells to five esophageal and one GEJ cancer cell lines, providing a proof of principle concept.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were housed 2~3 animals per cage in pathogen free conditions, under 12 h light/dark cycle, 22 ± 2°C room temperature, and 40–60% relative humidity with ad libitum food and drinking water. Orthotopic esophageal cancer model was performed according to a previous study [21]. A skin incision was made in the middle of the upper abdomen from the xiphoid process.…”
Section: Methodsmentioning
confidence: 99%